2020
DOI: 10.1088/1361-6528/ab8ee1
|View full text |Cite
|
Sign up to set email alerts
|

The important role of strain on phonon hydrodynamics in diamond-like bi-layer graphene

Abstract: In this work, combining first-principles calculation and the phonon Boltzmann transport equation, we explored the diffusive thermal conductivity of diamond-like bi-layer graphene. The converged iterative solution provides high room temperature thermal conductivity of 2034 W mK−1, significantly higher than other 2D materials. More interesting, the thermal conductivity calculated by relaxation time approximation is about 33% underestimated, revealing a remarkable phonon hydrodynamic transport characteristic. Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…First, in contrast to graphene, in phosphorene and monolayer MoS 2 , the twelve atoms in the unit cell leads to thirty-six phonon branches. It was found that a complex crystal with many optical modes is usually associated with low lattice thermal conductivity ( Ding et al, 2018 ; Hu et al, 2020a ; Hu et al, 2020b ). A number of optical modes gather in frequency about 10 THz.…”
Section: Resultsmentioning
confidence: 99%
“…First, in contrast to graphene, in phosphorene and monolayer MoS 2 , the twelve atoms in the unit cell leads to thirty-six phonon branches. It was found that a complex crystal with many optical modes is usually associated with low lattice thermal conductivity ( Ding et al, 2018 ; Hu et al, 2020a ; Hu et al, 2020b ). A number of optical modes gather in frequency about 10 THz.…”
Section: Resultsmentioning
confidence: 99%
“…The deformation of diamanes can significantly influence their thermal conductivity [13]; it is predicted that under 5% tensile strain, at room temperature, the thermal conductivity (1081 W/mK) is only about 50% of that of a strain-free sample, and under 20% strain, it is dramatically reduced to only about 11% (226 W/mK). Under applied external strain of 5% leads to the underestimation of the relaxation time with thermal conductivity reduction to 20% compared with strain-free condition.…”
Section: Multilayer Diamanes-theoretical Studiesmentioning
confidence: 99%
“…Among the diamane, a structure with only one functionalized surface was also predicted, while an opposite surface was represented as an array of dangling bonds; this unique structure was called "diamondene" [7]. The unique properties of predicted and experimentally synthesized 2D diamonds-such as the high thermal conductivity [8][9][10][11][12][13], high hardness [3,14,15], excellent properties for electromechanical vibrators [12], optic peculiarities [16][17][18], and wide-gap spectra with many resonance peaks in valent and conductive bands in the density of states [17,18]-make such structures promising candidates for the main components in future nanoelectronics, optics and photonics.…”
Section: Introductionmentioning
confidence: 99%
“…8 Inspired by the ultra-high thermal conductivity of graphene, 9 the researches on thermal transport in low-dimensional system have attracted extensive attention. [10][11][12][13][14][15][16] The decreased dimension induces quantum connement effect and alters the phonon dispersion, which further results in unique lattice thermal transport features. 17 In addition to graphene, Sahin et al 18 has proposed 13 different 2D III-V compounds of honeycomb lattice, seven of which (AlN, GaN, InN, BN, BP, BAs and BSb) have planer structure like graphene.…”
Section: Introductionmentioning
confidence: 99%